Rapid method to extract DNA from Cryptococcus neoformans. - Varma, A (1991)
A rapid and easy method for the extraction of total cellular DNA from Cryptococcus neoformans is described. This procedure modifies and considerably simplifies previously reported methods. Numerous steps were either eliminated or replaced, including preincubations with cell wall permeability agents such as beta-mercaptoethanol and dithiothreitol. The commercially available enzyme preparation Novozyme 234 was found to contain a potent concentration of DNases which actively degrade DNA. Degradation and loss of DNA was prevented by maintaining a high concentration of EDTA in the lysing solution. This procedure resulted in high yields (150 to 200 micrograms of DNA from 100 ml of culture) of good-quality (undegraded), high-molecular-weight DNA which was readily digested by restriction endonucleases, making it suitable for use in various molecular applications.